2014
DOI: 10.4172/2155-983x.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Polydioxanone Nano-Fibers as Anti-Inflammatory Agents

Abstract: PDOPDO nano-fibers were a kind gift of Dongbang Acupuncture Ltd, Korea. Phagocytosis assayPhagocytosis was assessed by flow cytometry using pHrodo AbstractThe use of biodegradable polydioxanone (PDO) nano-fibers for various purposes is increasing but the effects of these fibers on immune responses are not well understood. We examined the potential stimulatory and inhibitory effects of PDO coated fibers on immune cell functions in vitro in humans and in vivo in mice. Short term in vitro exposure of human blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“… 28 Another animal study mentioned that the injection of PDO into mice with rheumatoid arthritis had an anti-inflammatory effect by increasing interleukin-10. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Another animal study mentioned that the injection of PDO into mice with rheumatoid arthritis had an anti-inflammatory effect by increasing interleukin-10. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Another polymer that has been investigated is polydioxanone (PDX) since electrospun PDX presents similar mechanical properties to collagen and elastin [167] and has been widely used in drug/gene delivery. Moreover, PDX nanofibers have been studied as anti-inflammatory agents [168] in rotator cuff repair [169]. For instance, Kratz et al [170] designed a diblock PCL-b-PDX nanofibrous scaffold that revealed values of R f and R r in the range of 92-98%.…”
Section: Drug Deliverymentioning
confidence: 99%
“…The materials from which the lifting threads are made seem to be neutral in terms of triggering autoimmune reactions and some of them are even used in the treatment of autoimmune diseases by blocking autoimmune systemic response [81,82]. Autoimmune diseases, however, are a relative contraindication-the safety of the thread has not been established in these patients.…”
Section: Lifting Threadsmentioning
confidence: 99%